Even a Chronic Mild Hyperglycemia Affects Membrane Fluidity and Lipoperoxidation in Placental Mitochondria in Wistar Rats - Figueroa-García, María del Consuelo (PLoS One, 2015)
It is known the deleterious effects of diabetes on embryos, but the effects of diabetes on placenta and its mitochondria are still not well known. In this work we generated a mild hyperglycemia model in female wistar rats by intraperitoneal injection of streptozotocin in 48 hours-old rats. The sexual maturity onset of the female rats was delayed around 6–7 weeks and at 16 weeks-old they were mated, and sacrificed at day 19th of pregnancy. In placental total tissue and isolated mitochondria, the fatty acids composition was analyzed by gas chromatography, and lipoperoxidation was measured by thiobarbituric acid reactive substances. Membrane fluidity in mitochondria was measured with the excimer forming probe dipyrenylpropane and mitochondrial function was measured with a Clark-type electrode. The results show that even a chronic mild hyperglycemia increases lipoperoxidation and decreases mitochondrial function in placenta. Simultaneously, placental fatty acids metabolism in total tissue is modified but in a different way than in placental mitochondria. Whereas the chronic mild hyperglycemia induced a decrease in unsaturated to saturated fatty acids ratio (U/S) in placental total tissue, the ratio increased in placental mitochondria. The measurements of membrane fluidity showed that fluidity of placenta mitochondrial membranes increased with hyperglycemia, showing consistency with the fatty acids composition through the U/S index. The thermotropic characteristics of mitochondrial membranes were changed, showing lower transition temperature and activation energies. All of these data together demonstrate that even a chronic mild hyperglycemia during pregnancy of early reproductive Wistar rats, generates an increment of lipoperoxidation, an increase of placental mitochondrial membrane fluidity apparently derived from changes in fatty acids composition and consequently, mitochondrial malfunction.